Perspectivas e desafios de idosos sobre o uso de tecnologias digitais: narrativas e letramentos - Lúcia Urbano de Carvalho Guedes (2023)
The present research is characterized as a study focused on the elderly subject and their digital inclusion, aiming to understand the phenomenon of the migration of elderly people to the digital age from the narratives of the subjects themselves. The guiding objective is to report and expose the experiences lived by the elderly in the digital age and its effects on their daily life, regarding the impacts on their sociability and informational behavior. The option to carry out the study with elderly users, the so-called “third age” or “better age”, is justified by the fact that life expectancy is proportionally inverse to the speed and dimension that technology reaches in today's society. Thus, assuming as a fundamental assumption the understanding of the elderly as active beings, it is up to us to problematize how the migratory process of the elderly is being carried out, through advances and challenges proposed by the digital culture. The research is characterized by a qualitative study and descriptive investigation, having as methodological instruments the questionnaire and the interview. The sample is composed of 12 (twelve) invited elderly people, aged between 60 and 80 years, educated or not educated, retired or in activity, of both sexes. To support the discussions, we rely on studies by CASTELLS (2007, 2020), LÉVY (1993, 1996), SOARES (1998, 2002) and FREIRE (1992, 2005). We understand that the study of this focus group and its behavioral specificities can significantly contribute to making the mediation between technology and the elderly increasingly accessible and effective.